Global Research Trends in Laboratory Diagnosis of Pediatric Iron Deficiency Anemia: A Bibliometric Analysis - Tika Adilistya; Firman Pribadi; Oktien Harsari Prananingsih (Universitas Pahlawan Tuanku Tambusai, 2026)
Iron deficiency anemia (IDA) remains one of the leading causes of anemia among children worldwide, making accurate laboratory diagnosis essential for timely management. This study aimed to evaluate global research trends, scientific collaboration, and emerging themes in the laboratory diagnosis of pediatric IDA using a bibliometric approach. A bibliometric analysis was conducted using Scopus-indexed publications published between 2016 and 2026. Eligible original articles and review papers were analyzed using Bibliometrix/Biblioshiny and VOSviewer to examine publication growth, leading journals, author productivity, international collaboration, and keyword co-occurrence. A total of 1,955 publications from 777 journals involving 10,032 authors were included. The average number of authors per document was 6.19, with international collaboration accounting for 22.25% of publications. Nutrients, The Journal of Nutrition, and BMC Pediatrics were the most productive journals. Bradford’s Law demonstrated a dispersed publication pattern across journals, while Lotka’s Law indicated that most authors contributed only a single publication. Keyword analysis revealed a shift from conventional diagnostic markers, including ferritin and transferrin saturation, toward emerging biomarkers such as reticulocyte hemoglobin, hepcidin, and soluble transferrin receptor, reflecting increasing interest in improving diagnostic accuracy. These findings provide a comprehensive overview of the evolving research landscape and may support future studies, diagnostic standardization, and evidence-based clinical practice in pediatric IDA.